Epidemiological Situation on Natural Focal Viral Infections in the Territory of the Stavropol Region - N. G. Varfolomeeva; A. V. Ermakov; N. F. Vasilenko; G. P. Shkarlet; O. V. Maletskaya; O. A. Kireitseva; I. N. Zaikina; A. N. Kulichenko (Проблемы особо опасных инфекций, 2011)
Landscape-geographical and climatic peculiarities of the Stavropol Region, high abundance of mosquito and ticks, the diversity of wild mammal and bird species, developed agriculture and infrastructure create favorable conditions for circulation of arboviruses and hantaviruses, emergence of cases of viral infections, which sometimes cause serious epidemic complications. CHF natural focus actively functions in the territory of the Stavropol Region at present. Detected is presence of West Nile fever, tick-born encephalitis, Batai fever agents and specific antibodies, as well as hemorrhagic fever with renal syndrome agent.